Reduction in unnecessary CT scans for head-injury in the emergency department using an FDA cleared device - Naunheim, Rosanne; Konstantinovic Koscso, Monique; Poirier, Robert (The American journal of emergency medicine, 2019)
Two potential initial evaluation pathways were compared for CT referrals: a.Clinical Site Practice Referral: Relying on clinical judgement of the ED physician according to site standard of care. b.EEG Based Classification Algorithm Assessment: Relying on the ternary output of the SIC (positive, negative, equivocal) to inform CT referral decision. Using the second pathway with input from the EEG based classification algorithm assessment (SIC) resulted 63 of the patients to be positive for CT referral. [...]the use of the EEG Based Algorithm decision pathway to aid in referral for CT scanning would have resulted in 63 patients being referred for CT scans instead of 91 referrals made following standard clinical site practice. The integration of such a rapidly obtained, objective biomarker from the BrainScope One device in the initial assessment of mTBI patients shows promise to aid in reduction of unnecessary radiation exposure and to speed up throughput times for these patients, thus, reducing overall cost to the health system.Sources of support Washington University School of Medicine Division of Emergency Medicine was reimbursed by BrainScope at a fair market value commensurate with their time and effort in entering the de-identified patient data into the Registry.